Opposite Expression of Hepatic and Pulmonary Corticosteroid-Binding Globulin in Cystic Fibrosis Patients - Tchoukaev, Anastasia; Taytard, Jessica; Rousselet, Nathalie; Rebeyrol, Carine; Debray, Dominique; Blouquit-Laye, Sabine; Moisan, Marie-Pierre; Foury, Aline; Guillot, Loic; Corvol, Harriet; Tabary, Olivier; Le Rouzic, Philippe (Frontiers in Pharmacology, 2018)
Cystic fibrosis (CF) is characterised by a chronic pulmonary inflammation. In CF, glucocorticoids (GC) are widely used, but their efficacy and benefit/risk ratio are still debated. In plasma, corticosteroid-binding globulin (CBG) binds 90% of GC and delivers them to the inflammatory site. The main goal of this work was to study CBG expression in CF patients in order to determine whether CBG could be used to optimise GC treatment. The expression of CBG was measured in liver samples from CF cirrhotic and non-CF cirrhotic patients by qPCR and Western blot and in lung samples from non-CF and CF patients by qPCR. CBG binding assays with 3H-cortisol and the measurement of the elastase/α1-antitrypsin complex were performed using the plasmas. CBG expression increased in the liver at the transcript and protein level but not in the plasma of CF patients. This is possibly due to an increase of plasmatic elastase. We demonstrated that pulmonary CBG was expressed in the bronchi and bronchioles and its expression decreased in the CF lungs, at both levels studied. Despite the opposite expression of hepatic and pulmonary CBG in CF patients, the concentration of CBG in the plasma was normal. Thus, CBG might be useful to deliver an optimised synthetic GC displaying high affinity for CBG to the main inflammatory site in the context of CF, e.g., the lung.